Essays. - Edbury, P. W. (Peter W.), author. ([S.l.])
1 online resource
Keywords: This second collection of papers by Peter Edbury focuses primarily on the literature either composed in the Latin East or closely associated with it. The legal treatises from the kingdom of Jerusalem and from Cyprus and Antioch have long been recognized as providing insights into the juridical and social history of these places in the twelfth and thirteenth centuries, and some of the papers re-issued here reflect the author's work in re-editing two of the most famous of these treaties, those by John of Ibelin-Jaffa and Philip of Novara. The studies on historical literature are chiefly concerned with vernacular texts, most notably the Old French translation of William of Tyre and its Continuations, again much a result of his current work on a new edition of the Continuations and the associated text known as La Chronique d'Ernoul. Other papers concerned with aspects of the narrative traditions that furnish a significant part of our knowledge of Lusignan Cyprus in the thirteenth and fourteenth centuries, and with which in one way or another Peter Edbury has been engaged since the early 1970s.